Concept Acquisition of Rotational Dynamics by Interactive Demonstration and Free-Body Diagram - Ogi Danika Pranata; Lia Yuliati; Dr. Wartono (Intelektual Pustaka Media Utama, 2017)
The concepts of force and motion are essential material in physics. However, students experience many difficulties in the concept of force in rotational dynamics. This research was conducted to measure students’ concept acquisition of the rotational dynamics through Interactive Demonstration assisted by Free-body diagram. The mixed research method was chosen through the use of test instruments in the forms of 10 multiple-choice with open ended questions. The subjects of the research were 35 students XI IPA Senior High School 2 Sungai Penuh-Indonesia. Students’ concept acquisition was measured before and after the intervention to be analyzed quantitatively. The obtained N-gain score was 0.47, and it showed that there was a moderate improvement in students’ concept acquisition, while the effect size value was 1.82 showing that the intervention strongly affected students’ concept aquisition. The data were also supported by the results of the qualitative analysis of the students’ answers and worksheets given during the intervention process.